Stable word combinations сomprehensive dictionary as a source base for translation lexicographical works - Лучик, Алла Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
In Russian, Ukrainian, and Polish lexicographical work, all the preconditions for organizing a comprehensive stable word combinations dictionary have been formed. The these works registers in each Slavic linguistic school will have to be formed by various units of different types, which are characterized by the semantic integrity. First of all, it is planned to include word equivalents, phraseological units, terminological combinations, proverbs, sayings. The formed dictionaries will reflect the language processes dynamics because a significant part of their register units have a transitional status of existence, as a result of which this work will be useful for theoretical linguistics. However, first of all, the need of compiling this dictionary is caused by practical activities.In Russian, Ukrainian, and Polish basic monolingual dictionaries stable word combinations are presented quite fully, but the approaches to their organization are mostly understandable only to specialists. Users of these works have significant difficulties in finding any stable combination. This activity is somewhat facilitated by specialized dictionaries of various units, but even in this case, the user requires some linguistic training.Being organized according to a certain concept, a stable combinations comprehensive dictionary will greatly facilitate the user's search, especially translation activities, which are greatly complicated by the lack of dictionary registers for differently formed units. This is true for the translation from one Slavic language to another, as well as similar actions in the field of Slavic-Germanic and, of course, Slavic-Romance languages etc.In the proposed work it is proved that the compiled complex stable word combinations dictionaries in each separate Slavic language will become an important source for improvement of already created paper and on-line translation dictionaries.